Influence of Irrigation with NaOCl and Chlorhexidine on Microleakage - Mylona Zoumpoulia; Gogos Christos; Economides Nikolaos (Balkan Stomatological Society, 2015)
Background: Irrigation during endodontic therapy is required in order to remove debris, tissue remnants, microbes and smear layer. Sodium hypochlorite (NaOCl) and Chlorhexidine (CHX) are the most commonly used irrigants. Although they are reported to have good antimicrobial effects, both have limitations. Hence, a combination of NaOCl and CHX has been proposed to compensate for these limitations. However, this association forms a dense, orange-brown precipitate that stains walls of the pulp chamber. The aim of this study was to clarify in vitro if this precipitate affects the microleakage of endodontic sealers.